2014
DOI: 10.1088/0034-4885/77/4/046602
|View full text |Cite
|
Sign up to set email alerts
|

Shear thickening in concentrated suspensions: phenomenology, mechanisms and relations to jamming

Abstract: Shear thickening is a type of non-Newtonian behavior in which the stress required to shear a fluid increases faster than linearly with shear rate. Many concentrated suspensions of particles exhibit an especially dramatic version, known as Discontinuous Shear Thickening (DST), in which the stress suddenly jumps with increasing shear rate and produces solid-like behavior. The best known example of such counter-intuitive response to applied stresses occurs in mixtures of cornstarch in water. Over the last several… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
490
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 516 publications
(512 citation statements)
references
References 127 publications
(314 reference statements)
18
490
1
3
Order By: Relevance
“…The modeling, considering viscous interactions, was not able to produce a shear-thickening behavior. This result is consistent with the fact that the shear thickening response is not an intrinsic bulk material response but is related to interaction with the boundaries which confine the suspension (Brown and Jaeger [15] The interplay between yield stress and thixotropy is discussed in Møller et al [16] They argue that below a critical shear rate, all the flow is localized in a region near the shearing wall, and if the globally imposed shear rate is increased it is not the shear rate in the sheared region that increases but rather the extent of the sheared region which grows -to fill the entire gap of the shear cell exactly at the critical shear rate. (Note that this localization is distinct from wall slip).…”
Section: Connection With Discontinuous Shear Thickening In Dense Ssupporting
confidence: 88%
See 2 more Smart Citations
“…The modeling, considering viscous interactions, was not able to produce a shear-thickening behavior. This result is consistent with the fact that the shear thickening response is not an intrinsic bulk material response but is related to interaction with the boundaries which confine the suspension (Brown and Jaeger [15] The interplay between yield stress and thixotropy is discussed in Møller et al [16] They argue that below a critical shear rate, all the flow is localized in a region near the shearing wall, and if the globally imposed shear rate is increased it is not the shear rate in the sheared region that increases but rather the extent of the sheared region which grows -to fill the entire gap of the shear cell exactly at the critical shear rate. (Note that this localization is distinct from wall slip).…”
Section: Connection With Discontinuous Shear Thickening In Dense Ssupporting
confidence: 88%
“…Also in Jiang et al, [35] a suspension of cornstarch was found to exhibit discontinuous shear thickening (such as that we have observed for semisolid metals) for a volume fraction above 0.34, which is close to the 0.36 value we have been referencing for semisolid metals. As mentioned by Brown and Jaeger, [15] shear thickening starts to gradually appear at a packing fraction of typically around 0.3-0.4, and the slope on shear stress-shear rate curve increases with increasing volume fraction. [15,35] Jorstad et al [36] indicate that in thin sections, solid particles cannot migrate away from the deformation area, so solid-solid interactions increase, resulting in increase in viscosity and so the possibility to have laminar flow at very high velocities.…”
Section: E Yield Stress Masking Shear Thickening?mentioning
confidence: 57%
See 1 more Smart Citation
“…nonlinear rheology | hydration layer | shear thickening | elastic turbulence | dynamic force spectroscopy T he rheological nonlinearity of fluids (1-3) is a universal, highly nonequilibrium phenomenon observed in diverse systems ranging from soft materials [e.g., polymeric (1,4), biological (5,6), and colloidal (2,(7)(8)(9)) solution] to terrestrial layers [e.g., Earth's mantle (10)], occurring at extremely high shear rates (1,2,11). Although shear thinning (decrease of viscosity) originates from the decrease of particle density correlation (2,12), shear thickening (4,7,8,(13)(14)(15)(16)(17) (increase of viscosity) has been understood in various perspectives such as hydrodynamic instability (18) at high Reynolds number (Re) or order-disorder transition (13,14) at low Re and high Weissenberg number (Wi) [a measure of elasticity of viscoelastic flows (1); see SI Appendix, section S1, for nonlinear hydrodynamics formalism based on Re and Wi].…”
mentioning
confidence: 99%
“…Nevertheless, most work has focused on dry particulate systems (solid-gas) [37,42,43] and, more recently, colloidal and granular suspensions (solid-liquid) [44,45] because of the much simpler binary-phase scenario −even so, they are still poorly understood. The additional fluid phase in the unsaturated case strongly complicates the picture and justifies that, apart from the phenomenology, the physics of wet particulate systems have been little studied and remains largely unknown [35,46].…”
Section: Introductionmentioning
confidence: 99%